2013
DOI: 10.1159/000351036
|View full text |Cite
|
Sign up to set email alerts
|

Validation of RiskCheck Bladder Cancer ©, Version 5.0 for Risk-Adapted Screening of Bladder Cancer

Abstract: Introduction: The aim of the study was to assess the strength of the online tool RiskCheck Bladder Cancer©, version 5.0 (RCBC) for early detection of bladder cancer (BC). Materials and Methods: RCBC was evaluated retrospectively based on the data of 241 patients, of which 141 were suffering from BC. Statistical analysis was performed by descriptive statistics, nonparametric group comparison, classification tree analysis and ROC analysis. Results: ROC analysis of the risk classification showed a sensitivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For example, Vickers et al showed in a study which incorporated data from the prostate, lung, colorectal, and ovarian (PLCO) trial that screening for bladder cancer can be optimized when patients with elevated risk for bladder cancer are included in screening trials ( 3 ). Moreover, risk stratification tools such as the RiskCheck Bladder Cancer © which showed a high predictive power for the identification of asymptomatic patients living under risk of developing bladder cancer, can help to improve detection rates compared with the general population ( 4 ). It is important to identify patients, who are at elevated risk of harbouring bladder cancer due to smoking history, gender, age, exposure to bladder cancer inducing substances.…”
Section: Clinical Situationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Vickers et al showed in a study which incorporated data from the prostate, lung, colorectal, and ovarian (PLCO) trial that screening for bladder cancer can be optimized when patients with elevated risk for bladder cancer are included in screening trials ( 3 ). Moreover, risk stratification tools such as the RiskCheck Bladder Cancer © which showed a high predictive power for the identification of asymptomatic patients living under risk of developing bladder cancer, can help to improve detection rates compared with the general population ( 4 ). It is important to identify patients, who are at elevated risk of harbouring bladder cancer due to smoking history, gender, age, exposure to bladder cancer inducing substances.…”
Section: Clinical Situationsmentioning
confidence: 99%
“…Cystoscopy and adjunct to it the urine cytology, is currently the gold standard for the detection of bladder cancer, especially in patients with symptoms for bladder cancer such as haematuria. There is a limitation for the cystoscopy in the detection of flat lesions while the detection of carcinoma in situ (CIS) is the main domain of the urinary cytology ( 4 ). During the last years many urinary markers have been developed with the aim to identify bladder cancer before the lesion is visually detectable.…”
Section: Clinical Situationsmentioning
confidence: 99%
“…RC makes it possible to diagnose tumors early before symptoms occur. (3,4) Studies of RC have aimed to diagnose and treat tumors early by identifying the risk group. However, no risk estimation survey in which risk factors in patients with bladder cancer are evaluated together has been performed.…”
Section: Introductionmentioning
confidence: 99%